The Thinking Process of Al Quran in Preventing Hoax - Mujib Ridlwan; Yayuk Siti Khotijah (Dialogia: Islamic Studies and Social Journal, 2021)
This article explained the threat of hoax in social media towards Indonesia. Digital era is an era of the proliferation of information that every individual can convey information quickly and globally. The presence of global information certainly has side effects, both negative and positive effects. The example of positive effect is the teaching and learning process can still continue using online method during the covid-19 pandemic. The negative effect is there are many news that are not based on facts (hoaxes) that threaten the foundations of the state in Indonesia. The continuity of the nation and state in Indonesia is fractured because hoaxes. Hoaxes will continue and increase when the nation's major interests are contested, like when the presidential or regional head elections. Indonesia adheres to the principle of Bhinneka Tunggal Eka and consists of many tribes, traditions, and races, of course must be more careful in guarding and controlling hoaxes in order to maintain the Republic of Indonesia. The Islam conception in avoiding the danger of hoaxes becomes an alternative offer. We must be more careful in guarding and controlling hoaxes in order to maintain the Republic of Indonesia. The conception of Islam in avoiding the hoaxes becomes an alternative offer.